Perceptions of the crowded sky as assessed through response to aerial infrastructure - Kolbmann, Christina L.; Leslie, Carrie; Anderson, Chris; Kelly, Jeff F.; Ross, Jeremy D.; Jervis, Lori; Reedy, Justin; Bridge, Eli Samuel (Frontiers in Built Environment, 2023)
Ever increasing numbers of wind turbines, communication towers, power lines, and aerial vehicles are clear evidence of our growing reliance on infrastructure in the lower aerosphere. As this infrastructure expands, it is important to understand public perceptions of an increasingly crowded sky. To gauge tolerance for aerial crowding, 251 participants from across the US completed a survey where they rated tolerance for a series of aerial infrastructure images (i.e. towers, turbines, and airborne vehicles) in four landscapes with varying degrees of pre-existing ground-level infrastructure that approximated rural, suburban, and urban settings. We predicted lower tolerance for aerial infrastructure (1) in more natural scenes and (2) among rural residents. In general, participants preferred an open aesthetic with relatively little aerial infrastructure across all landscape types. No clear association was found between infrastructure tolerance and natural scenes nor rural residency, with participants slightly less tolerant of infrastructure in the suburban scene. Tolerance scores were generally similar across age, income levels, and political affiliations. Women indicated less crowding tolerance than men, with this effect driven by a disproportionate number of women with zero tolerance for aerial infrastructure. African Americans and Asians had higher tolerance scores than other racial/ethnic groups, but these trends may have been affected by low sample sizes of non-white participants. Our survey revealed fewer differences in crowding tolerance across demographic groups than might be expected given widely reported political and geographic polarization in the U.S. Attitudes toward aerial infrastructure were varied with few associations with demographic parameters suggesting that public opinion has not yet solidified with regard to this issue, making possible opportunities for consensus building with regard to responsible development of aerial infrastructure.